Design of Remote Monitoring Iot System Based on 5G and New Optical Fiber Intelligent Structure - Lei Hu (Advances in Materials Science and Engineering)
In recent years, with the progress and development of social science and technology, remote monitoring of Internet of Things systems has attracted more and more attention. The remote monitoring system is mainly a network system with convenient layout, simple maintenance, and high security performance built on the basis of the wireless network, which can realize real-time monitoring, and collects transmit information. It is mostly used in remote monitoring of room temperature, remote monitoring of intelligent furniture, engineering construction, and teaching. Communication technology dominates the operation of remote monitoring systems. With the introduction of 5G technology, mobile Internet technology has been pushed to the top of technology again. Using 5G mobile communication technology in the monitoring system, people can observe or operate the monitored things at any time. The sensor is an indispensable component of the remote monitoring system, and a new type of optical fiber is added to the sensor to make the system function more complete. However, the related technology is not very mature, and the research on remote monitoring system is relatively backward in China. Relevant studies have found that when the remaining energy of the information node in the remote monitoring system reaches 10%, the information node will die and the speed of information transmission will decrease. Therefore, adding new technologies is conducive to improving the performance of remote monitoring systems.